Answer:
y - 5 = 3(x - 4)
y - 5 = 3x - 12
y = 3x - 7
Step-by-step explanation:
Answer:
x^2-2x=10
a few more steps...
the answer is 1+the square root of 11
Answer:
2x + 12 = 64
x = 26 (mark brain if this helps and is correct)
Step-by-step explanation:
to solve equations with one missing variable we must use the order of operations of equality
step 1: use the subtraction property of equality meaning subtract each side of the equation
ex: 2x + 12 - 12 = 64 - 12 (2x = 52)
step 2: use the division property of equality meaning divide each side of the equation by 2
ex: 2x/2 = 52/2 (x = 26)
step 3: check your answer by putting 26 as x because that is our answer
2(26) + 12 = 64 (multiply 2 * 26)
52 + 12 = 64 (add 52 + 12)
64 = 64 (if both sides of the equation are the same number like 64 = 64 then your answer is true meaning that x is equal to 26)
Answer: the slope is 1
Step-by-step explanation:
Answer: I think the answer might be the first option
Step-by-step explanation: